2021
DOI: 10.3390/su13063114
|View full text |Cite
|
Sign up to set email alerts
|

Clean Energies for Ghana—An Empirical Study on the Level of Social Acceptance of Renewable Energy Development and Utilization

Abstract: Despite the enormous renewable energy (RE) resources available in Ghana, the country has not seen much development and investments in the sector. Therefore, the government has committed to increasing the share of RE in the country’s electricity generation mix to some 10% by 2030. However, this cannot be achieved without the Ghanaian people’s support since the RE sector is capital intensive and requires both public and private sector participation. This study was conducted to evaluate RE’s social acceptance amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Nonetheless, after the series' first difference is taken, all the series are stationary at first difference. We progressed to the cointegration test after confirming that the series is of order (1). The bounds test outcomes are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, after the series' first difference is taken, all the series are stationary at first difference. We progressed to the cointegration test after confirming that the series is of order (1). The bounds test outcomes are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Climate change has made sustainable development the primary policy aim, with the objective of reducing greenhouse gas (GHG) emissions [ 1 , 2 ]. China, the globe’s second-biggest economy, is confronted with several environmental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The Ghana national agenda to achieve 10% increase in renewable energy utilization by 2030 has increased the awareness of the public social acceptance and making the aware of the benefits. Citizen's acceptance to the use of renewable energy increases the demand for the energy and therefore giving confidence to the financing institutions to invest on the resource [105] . The national policy emphasizes on regenerating biofuels and on the other hand the country has great potential in biomass a management and generating energy from waste hence greater advantage for renewable energy in the country [106] .…”
Section: Merits Of the Renewable Energy Issues In Ghanamentioning
confidence: 99%
“…The demand for renewable energy is rising globally, making it imperative to understand users' attitudes and intentions towards renewable energy. Several acceptance studies have been conducted using varied methods to explain users' attitudes and their intentions to use renewable energy [25][26][27][28][29]. Most of these studies find some level of acceptance of renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies find some level of acceptance of renewable energy. Agyekum et al [29] found a general level of acceptance of renewable energy in Ghana, with varying acceptance levels among different individuals. Ahmad et al [26] reveal that attitude, perceived ease of use, and perceived usefulness have a significant impact on the intention to use solar photovoltaic technology in Malaysia.…”
Section: Introductionmentioning
confidence: 99%